IMPACT OF TOURISM ON ECONOMIC GROWTH IN CROATIA - Hajdinjak, Sanja (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL)
Although impact of tourism on the economy has been researched in the literature, the results of studies deliver varying conclusions leaving the field open to further studies. While the literature has so far dealt with cases of large tourism sectors, there has been no research on cases of dominant tourism sector in transitional post-socialist economies. Tourism certainly plays an important role in the Croatian economy, but so far research tested the impact it actually has on economic growth. This paper attempts to fill this gap by testing what is the long-term impact of tourism on growth of GDP. The author tests whether tourism enables increase in level of productive factors and indirectly ensures long-term development (TKIG hypothesis), or it contributes by delivering short-term profits. The results of the paper imply that TKIG hypothesis is confirmed in the case of Croatia. Tourism receipts can enable increase in capital goods imports and there is a mechanism through which increase in tourism specific productive factors leads to economic growth. However, the organization of the tourism sector, as well as political elite’s attitudes towards tourism have an important effect on determining impact tourism has on the economy.